Tlingit canoe carrying many people pushes off from shore, Wrangell, Alaska, 1887 - Partridge, William H.
Large canoe with carved prow (and American flag flying in stern) sets off from shore carrying men & women in western-style clothing. Behind them on shore is a carved whale. Wrangell visible in background across water. Caption on mount: Alaska, U.S. Ft. Wrangel. Partridge Publisher. 69 Morrison St., Portland, Or. PH Coll 322.12